Um estudo sobre os fatores organizacionais que influenciam a gestão de portfólio de projetos de TIC - Larieira, Cláudio Luís Carvalho (2013)
Organizations may manage their operations more efficiently and leverage business strategies through Information and Communications Technologies (ICT), enabling them to add competitive advantages required for success and enterprise sustainability. Scholars and business leaders often dispute the value ICT brings to businesses because of high investment required for acquisition, implementation, and maintenance. Markowitz’s Portfolio Analysis dealt with financial investments. Other authors extended his proposition to project’s assessment, selection and prioritization, creating Project Portfolio Management. Subsequently, the concept was applied to ICT Project Portfolio Management was proposed. Various organizational factors can influence the execution of this process, beyond inherent technical and methodological issues. This thesis identified organizational factors that affect ICT Project Portfolio Management and analyzed their influence on the process. The research is of an applied nature, qualitative, exploratory and descriptive, and was executed in multiple case studies through analysis of three mid-sized commercial Brazilian banks. This thesis’ main contribution is reached through the creation of a conceptual structure that represents various organizational factors that influence ICT Project Portfolio Management. There are indications that organizational factors have great influence on this process, given the responses obtained in interviews with professionals of the banks analyzed.